Biofilm Inhibition Activity from Obligate Marine Fungi Against Pathogenic Vibrio Bacteria in Whiteleg Shrimp, Penaeus vannamei - Kristina, Kristina; Soowanayan, Chumporn; Suetrong, Satinee; Budiharjo, Anto; Rukmi, Isworo (Berkala Bioteknologi, 2022)
Early mortality syndrome (EMS) is caused by toxic strains of Vibrio bacteria that are produced when bacteria colonize and form biofilm in the digestive tract of cultivated shrimp. One possible control strategy for shrimp Vibriosis is biofilm inhibition. In the present study we tested cell-free culture broth (CF-CB) of 31 strains obligate marine fungi for its ability to inhibit growth and biofilm formation with 2 isolates of Vibrio bacteria, Vibrio harveyi (VH1) and Vibrio parahaemolyticus (3HP). CF-CB with the highest biofilm inhibitory activity were then prepared as feed additives and mixed with commercial feed (1 ml to 1 g ratio) to examined its potency on Vibrio-challenged shrimp. The supplemented feed were administered to post-larvae (PL) shrimps for 7 days before and after they were challenged with VH1 and 3HP which shrimp health and mortality were monitored. Overall, CF-CB from 9 out of 31 isolates examined inhibited biofilm formation by VH1 and 17 out of 31 isolates inhibited biofilm formation by 3HP. Survival rate in the un-challenged negative control was 66% while PLs fed with MCR00984 (Linocarpon appendiculatum) and challenged with VH1 and 3HP were 42% and 60% which was not significantly different (p≥0,05). This results shows some promise for possible application against Vibriosis in shrimp.